House of splendid isolation - O'Brien, Edna. (London : Phoenix, 1994)
An IRA terrorist, McGreevy, invades Josie's remote old house outside an Irish village, and their coexistence begins as a hostile standoff and evolves into something far more ambiguous.
Keywords: Country homes -- Fiction; 18.05 English literature